Anwā’u al-Ikhtibārāt wa al-Mustawiyāt al-Mi’yāriyyah li Mahārah al-Kalām fī al-Lugah al-‘Arabiyyah: The Types of Tests and Standard Levels of Speaking Skill in the Arabic Language - Mahmudi, Ihwan; Nurbaha, Ayu (Study Program of Arabic Language Teaching, 2023)
One of the important components of Arabic Language learning is speaking skills. To determine the success of teaching speaking skills, a teacher needs to evaluate the form of a test. This research aims to determine the types of tests for speaking skills and the standard assessment criteria. The method of this research is library research with a descriptive analysis approach. The primary data source in this research is the book Linguistic Tests, and the secondary data source is books related to learning speaking skills in Arabic. The data collection technique in this research is through books, documentation, articles, and journals related to research. The data analysis technique uses content analysis. The results of this research show that the types of tests in speaking skills are pronunciation tests, oral sentence structure tests, tests on the use of visual stimuli, and expression delivery tests. The standard criteria for assessment of speaking skills include standards for introduction, spoken language, and standards for structure. Linguistics, standards for body language, standards for ideas, standards for conversational etiquette, standards for using means of persuasion, standards for using various means of presentation, Standards for interpretation skills during presentations, and standards for delivery.